The Sedimentary Process of Sand Deposits in Bogowonto River, Purworejo, Central Java, and Progo River, Kulonprogo, Yogyakarta Using Granulometric Analysis - Nugroho, Muchamad Ocky Bayu; Rizkianto, Yody; Yuditama, Riyan Ranggas; Ryan, Akbar; Maulana, Agam (BRIN Publishing, 2021)
Sedimentation is the most traditional separation technique and it is relying on efficient coagulation and flocculation to produce flocs with good settling properties. Bogowonto River and Progo River belong to South Serayu Area. There are similar geological processes that affected the river forming process i.e., erosional process, provenance, and fault systems. The sand sedimentation process for each river could be different due to geometry and river morphology. This research aims to reveal the possible parameters that affected the sedimentary process and sediment material along the stream river. Granulometric analysis was done in this research. Samples were taken from 3 points (upstream, middle, and downstream) of Bogowonto river and Progo river. Statistically, the upstream and middle stream of Bogowonto River shows more dunes and beach environment characters than Progo River. It could be interpreted if Bogowonto has more deposit plain like point bar than Progo River. The downstream area has been interpreted as the upper part of estuarine due to river and beach environment. The volcanic arc (Tertiary & Quarternary) is the main sediment source for these rivers. The sediment supply of the Progo River is strongly influenced by Merapi’s eruption whereas Bogowonto river is dominated by reworked Old Andesite Formation (OAF) & Sumbing’s material. Morphologically, Bogowonto has more meandering features than Progo that indicates the development of river stage in a long time and wide distributed sediment materials.